Toxic response of the freshwater green algae Chlorella pyrenoidosa to combined effect of flotation reagent butyl xanthate and nickel. (1st October 2021) - Li, Hao; Yao, Jun; Duran, Robert; Liu, Jianli; Min, Ning; Chen, Zhihui; Zhu, Xiaozhe; Zhao, Chenchen; Ma, Bo; Pang, Wancheng; Li, Miaomiao; Cao, Ying; et al.
Abstract: Butyl Xanthate (BX) is a typical flotation reagent used to extract non-ferrous nickel ores, discharged into the surrounding environment of mining areas in large quantities. However, few studies have focused on the toxicity of combined pollution of BX and nickel (Ni) on aquatic plants, especially phytoplankton, the main producer of aquatic ecosystems. The toxicity and potential mechanism of single and combined pollution of BX and Ni at different concentrations (0–20 mg L −1 ) on typical freshwater algae ( Chlorella pyrenoidosa ) were studied. BX slightly stimulated the growth of C. pyrenoidosa on the first day, but Ni and Ni/BX mixture significantly inhibited it during incubation. Results showed that the inhibition rate ( I ) of the pollutants on the growth of C. pyrenoidosa followed the order: Ni/BX mixture > Ni > BX. The 96-h 20% effective inhibitory concentrations (96h-EC20 ) of Ni and BX on C. pyrenoidosa growth were 3.86 mg L −1 and 19.25 mg L −1, respectively, indicating C. pyrenoidosa was sensitive to pollutants. The content of total soluble protein (TSP) and chlorophyll a (Chl-a) changed significantly, which may be caused by the damage of pollutants to cell structures (cell membranes and chloroplasts). In addition, the I of pollutants on C. pyrenoidosa growth was related to dose, superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA). The increasement of reactive oxygen species (ROS), antioxidant enzymes (SOD and CAT), and MDA content, suggested C. pyrenoidosa suffered from oxidative stress, leading to lipid oxidation. These results will help to understand the toxicity mechanism of pollutants in typical mining areas and assess the environmental risks of pollutants to primary producers in aquatic ecosystems. Graphical abstract: Image 1 Highlights: First study on the toxic effects of Ni, BX, and Ni/BX mixture on C. pyrenoidosa. Ni/BX mixture was more toxic than Ni and BX on C. pyrenoidosa. Ni and BX disturbed enzyme activities to inhibit algae growth. Increased ROS level in algae cell led to oxidative stress and lipid peroxidation.